Main findings report of the RDP impact assessment study: February 1995 - Mustafa, Shams; Ara, Ishrat (© BRAC, 2016)
1. Introduction 2. RDP's impact on the material well-being of members 3. RDP's impact on vulnerability and coping capacity 4. Changes in women's lives 5. Institution building 6. The non-formal primary education programme